Clinical outcome measures following plasma exchange for MG exacerbation. Issue 10 (27th September 2019) - Raja, Shruti M.; Howard, James F.; Juel, Vern C.; Massey, Janice M.; Chopra, Manisha; Guptill, Jeffrey T.
Abstract: Our objective is to report longitudinal results of the MG‐ADL, MG‐Composite, MG‐MMT, and MG‐QoL15 in an open‐label trial of therapeutic plasma exchange in myasthenia gravis. Ten MG patients experiencing exacerbation had assessments prior to, immediately following, and at selected time points post‐TPE. Changes from baseline to 2 weeks post‐TPE were: MG‐ADL median −5.0, P  < 0.0033, MG‐QoL15 median −13.0, P  < 0.001, MG‐MMT median −10.0, P  < 0.0001, and MG‐Composite median −10.0, P  < 0.005. TPE produced a rapid, clinically significant change in all instruments, indicating these outcome measures are robust endpoints for clinical trials of rapidly efficacious MG therapies.